Association of geriatric nutritional risk index with renal prognosis and all-cause mortality among older patients with chronic kidney disease: a secondary analysis of CKD-ROUTE study - Lei Chen; Mengyao Yan; Jie Li; Xue Zhao; Lu Zeng; Zhumei Gao; Hongli Jiang; Limin Wei (Renal Failure)
Objectives The aim of the study was to assess the association between the geriatric nutritional risk index (GNRI) and incidence of CKD progression, all-cause mortality, and cardiovascular events in the elderly patients with chronic kidney disease (CKD) before dialysis initiation.Methods We performed a post hoc analysis of the CKD-ROUTE database, which included 538 pre-dialysis CKD patients aged ≥65 years in this prospective cohort study. Associations between GNRI and clinical outcomes were estimated using Cox proportional hazards model analysis. Multivariable linear mixed regression models with random intercepts were used to assess the association between GNRI and estimated glomerular filtration rate (eGFR) decline per year.Results During the median follow-up period of 2.92 years, there were 123 (22.86%) CKD progression events, 44 (8.18%) deaths, and 76 (14.13%) cardiovascular events. After adjusting for multiple confounding factors, the hazard ratios (HRs) for CKD progression in patients with GNRI <92 were 1.99 (95% CI, 1.34–2.97; p < 0.001), when compared with a GNRI of ≥92. Patients with a lower GNRI also had a significantly greater rate of eGFR decline over time than well-nourished patients (mean annual difference, −1.69; 95% CI, −2.62 to −0.77; p < 0.001). In the secondary outcomes, this association was consistent for all-cause mortality. Moreover, the associations were generally consistent across several subgroup and sensitivity analyses.Conclusions The lower GNRI is significantly associated with higher risks of renal prognosis and all-cause mortality in elderly patients with CKD.